2017
DOI: 10.1038/s41598-017-07648-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct Studies on the Lithium-Storage Mechanism of Molybdenum Disulfide

Abstract: Transition metal sulfides are regarded as a type of high-performance anode materials for lithium ion batteries (LIBs). However, their electrochemical process and lithium-storage mechanism are complicated and remain controversial. This work is intended to give the direct observation on the electrochemical behavior and find out the lithium-storage mechanism of molybdenum disulfide (MoS2) using in situ transmission electron microscopy (TEM). We find that single-crystalline MoS2 nanosheets convert to Mo nanograins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 43 publications
(32 reference statements)
1
65
0
Order By: Relevance
“…In the second and subsequent cathodic scans, the reduction peaks shift to around 1.0 and 1.8 V, indicating that lithiation mechanisms in the second and the subsequent cycles are different from the first cycle. In the subsequent anodic scans, the oxidation peaks at ≈1.5 and 2.29 V should be related to the oxidation of Mo nanoparticles to the MoS 2 phase . The sharp peak at 0.25 V corresponds to lithium‐ion extraction from CC .…”
Section: Resultsmentioning
confidence: 98%
“…In the second and subsequent cathodic scans, the reduction peaks shift to around 1.0 and 1.8 V, indicating that lithiation mechanisms in the second and the subsequent cycles are different from the first cycle. In the subsequent anodic scans, the oxidation peaks at ≈1.5 and 2.29 V should be related to the oxidation of Mo nanoparticles to the MoS 2 phase . The sharp peak at 0.25 V corresponds to lithium‐ion extraction from CC .…”
Section: Resultsmentioning
confidence: 98%
“…The structural evolution of MoS 2 electrodes has been intensively studied by using a number of in/ex situ characterization methods and theoretical calculations . The structural stability of commercial micrometer‐sized MoS 2 cycled in different voltage ranges was studied by Chen and co‐workers (Figure ) .…”
Section: Charge Storage In Libsmentioning
confidence: 99%
“…However, recent experimental studies have established this to be a real-life phenomenon. Su et al 33 observed in their in situ transmission electron microscopic (TEM) study that single-crystalline MoS 2 nanosheets convert to Mo nanograins with broken Mo-S bonds which helps in forming an Li 2 S matrix for the nanograins after the first full lithiation. After the delithiation, they observed the disappearance of the Li 2 S phase and We define the adsorption energy (E ads ) for the multi-Li adsorbed ReS 2 phases as…”
Section: Study Of Single LI Adsorption and Diffusion Barriersmentioning
confidence: 99%
“…(ii) It is difficult to find single Li binding sites on distorted crystals, which further inhibits the calculation of the diffusion barriers. Furthermore, recent in situ 33 and ex situ 34 measurements demonstrate metal-sulphur bond breaking during lithiation and restoration during delithiation process in TMD anode-based LIBs. None of those earlier studies consider such bond breaking in their firstprinciples based calculations.…”
mentioning
confidence: 97%